Impact of the Cardiovascular Health Integrated Lifestyle Diet on nutritional profile and dietary compliance in Ukrainian pediatric patients with heterozygous familial hypercholesterolemia - T. Marushko; T. Kurilina; Y.-E. Kulchytska (Zdorovʹe Rebenka, 2022)
Background. Hypercholesterolemia is a risk factor for atherosclerosis and cardiovascular disease; it is also a significant contributor to mortality from major adverse cardiovascular events. Medical nutrition therapy and proper physical activity level are all important parts of prevention strategy for patients with familial hypercholesterolemia (FH). The aim of our study was to determine the impact of the Cardiovascular Health Integrated Lifestyle Diet (CHILD-1) on the nutritional profile of patients with FH compared to the healthy peers and to identify possible deviations from the required daily nutrient intake. Materials and methods. Fifteen patients with FH included in the study were interviewed using an adapted Food Frequency Questionnaire. Their nutritional status was assessed with Anthro+ WHO software. The average daily intake of FETA nutrients and its possible correlation with other parameters were analyzed using SAS OnDemand for Academics software. Results. The results suggest a lack of complete dietary compliance in all age groups of patients. Patients with FH aged 5–9 years consumed more fat than recommended daily intake level. There was a significant deficit in vitamin D. Children with FH aged 10–14 years consumed less carbohydrates and fats per day, showed the deficiencies in protein, calcium, iron, iodine, zinc, vitamin D. Patients with FH aged 15–18 years had a slightly increased daily intake of cholesterol and vitamin D deficiency. This age group was the only to exceed the recommended daily cholesterol intake level. Age and gender had no effect on nutrient intake (p > 0.05). A statistically significant gender difference in intake of certain nutrients was recorded at ages 5–9 and 10–14 years only in the group of patients with FH, with higher levels in male patients. Conclusions. The diets of patients with FH and healthy children in all age groups were unbalanced, containing little protein and many non-recommended ingredients. Non-adherence to dietary treatment in patients with FH is associated with a lack of motivation, inadequate education of children and parents and a general lack of medical attention. Treatment of these patients requires a multidisciplinary team with a family-oriented approach that is focused on self-management skills development in a child. The FH management guidelines should include provision of medical nutrition therapy and step-by-step monitoring of growth and development.